1995
DOI: 10.1007/bf00020983
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and properties of a rice gene encoding phenylalanine ammonia-lyase

Abstract: Phenylalanine ammonia-lyase (PAL) genomic sequences were isolated from a rice (Oryza sativa L.) genomic library using a PCR-amplified rice PAL DNA fragment as a probe. There is a small family of PAL genes in the rice genome. The nucleotide sequence of one PAL gene, ZB8, was determined. The ZB8 gene is 4660 bp in length and consists of two exons and one intron. It encodes a polypeptide of 710 amino acids. The transcription start site was 137 bp upstream from the translation initiation site. Rice PAL transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 50 publications
4
66
1
1
Order By: Relevance
“…Monolignol synthesis and hydroxycinnamoylCoA synthesis were expected to be up-regulated in the wild-type whole internode and F71 pith parenchyma, respectively, and the expression profiles of genes in the phenylpropanoid pathway were determined. Although many researchers have studied genes in the phenylpropanoid pathway in rice, in many cases only a subset of these genes were targeted, and not all of the genes in this pathway have been identified (Kawasaki et al 2006; Lee et al 2007Lee et al , 2008Ma 2007;Minami et al 1989;Tobias and Chow 2005;Zhang et al 2006;Zhao et al 2004;Zhu et al 1995). The list of phenylpropanoid pathway genes in rice and the corresponding probe sets was based on all of these studies and a report on Arabidopsis genes by Raes et al (2003) (Table S4).…”
Section: Phenylpropanoid Pathway Genesmentioning
confidence: 99%
“…Monolignol synthesis and hydroxycinnamoylCoA synthesis were expected to be up-regulated in the wild-type whole internode and F71 pith parenchyma, respectively, and the expression profiles of genes in the phenylpropanoid pathway were determined. Although many researchers have studied genes in the phenylpropanoid pathway in rice, in many cases only a subset of these genes were targeted, and not all of the genes in this pathway have been identified (Kawasaki et al 2006; Lee et al 2007Lee et al , 2008Ma 2007;Minami et al 1989;Tobias and Chow 2005;Zhang et al 2006;Zhao et al 2004;Zhu et al 1995). The list of phenylpropanoid pathway genes in rice and the corresponding probe sets was based on all of these studies and a report on Arabidopsis genes by Raes et al (2003) (Table S4).…”
Section: Phenylpropanoid Pathway Genesmentioning
confidence: 99%
“…PAL has been proven to be a key enzyme in pathogen defense and stress response [69,70]. ZB8 is a rice PAL gene and has been shown to be induced under wounding and fungal cell wall elicitor treatment [71]. Peroxidase genes are also a class of protective genes that are induced in plant defense response [5].…”
Section: Overexpression Of Oswrky03 In Rice Leads To Induced Expressimentioning
confidence: 99%
“…We treated these XopP Xoo -OX cells with a bacterial MAMP PGN. Quantitative RT-PCR indicated that the expression of two defence-related genes, Probenazole1 (PBZ1) 30 and Phenylalanine ammonia-lyase1 (PAL1) 31 , was significantly suppressed in the XopP Xoo -OX cells (Fig. 1g).…”
Section: Resultsmentioning
confidence: 99%